Tannic acid modified corrosion inhibitor loaded gel material, preparation method thereof and application of tannic acid modified corrosion inhibitor loaded gel material in self-repairing anti-corrosion coating

By using tanninic acid modified load corrosion inhibitor gel material in anticorrosion coating, the existing hydrogel materials have been solved, with complex process, poor thermal stability and low compatibility, and efficient self-repair and corrosion prevention effect has been achieved .

CN119410184APending Publication Date: 2025-02-11YANTAI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411245160.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing hydrogel materials have problems such as cumbersome process, poor thermal stability and low compatibility in the anti-corrosion coating, making it difficult to achieve efficient self-repair and corrosion-proof effects.

Method used

PHVA/PEI gels with pH sensitivity, high thermal stability and good compatibility were synthesized by one-step free radical polymerization method, and modified into tanninic acid-modified corrosion inhibitor gel material to increase load The amount of corrosion inhibitor and the corrosion resistance of the coating.

Benefits of technology

It achieves simple process, high load on corrosion inhibitors, good anti-corrosion performance and self-repair performance of the coating, significantly improving the protection performance and durability of the anti-corrosion coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410184A_ABST
    Figure CN119410184A_ABST
Patent Text Reader

Abstract

The invention provides a tannic acid modified corrosion inhibitor loaded gel material as well as a preparation method and application thereof in a self-repairing anti-corrosion coating, and belongs to the technical field of anti-corrosion coatings. The preparation method comprises the following steps: mixing a reaction monomer, benzotriazole, an initiator and an organic solvent, and carrying out polymerization reaction to obtain hydrogel; the reaction monomers comprise hydroxypropyl acrylate, vinyltriethoxysilane, acrylic acid and polyethyleneimine; and mixing the hydrogel with a dispersing solvent, mixing the obtained suspension with a tannic acid solution, and modifying to obtain the tannic acid modified corrosion inhibitor loaded gel material. The prepared tannic acid modified corrosion inhibitor loaded gel material has good compatibility with an EP coating and good dispersity in the coating, and the corrosion inhibition performance of a corrosion inhibitor BTA can be improved. The corrosion inhibitor loading capacity in the coating is high, BTA molecules and TA molecules can be gradually released, and the self-repairing function is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion coatings, and in particular to a tannic acid-modified corrosion inhibitor-loaded gel material, a preparation method thereof, and an application thereof in a self-repairing anti-corrosion coating. Background Art

[0002] Carbon steel is one of the most widely used metal materials and is widely used in chemical, mining and construction industries. However, the corrosion of carbon steel can significantly reduce its strength, toughness and safety, leading to catastrophic failure or other serious consequences. Therefore, the development of green and efficient anti-corrosion technology is of great significance to inhibit the corrosion of carbon steel.

[0003] Organic anti-corrosion coatings have been widely used in the field of metal anti-corrosion. They can act as a physical barrier to resist the external corrosive environment and protect the metal substrate from the attack of corrosive substances. However, organic coatings will produce cracks during service, resulting in reduced anti-corrosion performance. Therefore, it is of great significance to develop anti-corrosion coatings that can self-repair during use.

[0004] Self-healing coatings can respond to local environmental changes related to the corrosion process, such as changes in ionic strength, pH value, and potential, and release repair factors to provide continuous protection for the metal matrix. In recent years, the preparation of smart materials loaded with corrosion inhibitors for coating self-repair has attracted more and more attention from scholars. Polymer gels with three-dimensional network structures have been used as self-healing materials in the design of anti-corrosion coatings. However, most of the current hydrogel materials not only have shortcomings such as cumbersome synthesis processes, but also have disadvantages such as poor thermal stability and low compatibility with organic coatings. Summary of the invention

[0005] The purpose of the present invention is to provide a tannic acid modified corrosion inhibitor loaded gel material and a preparation method thereof and application in a self-repairing anti-corrosion coating, which has the advantages of simple process, high corrosion inhibitor loading, good coating anti-corrosion performance and self-repairing performance.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a tannic acid modified corrosion inhibitor loaded gel material, comprising the following steps:

[0008] Mixing reaction monomers, benzotriazole, an initiator and an organic solvent to carry out polymerization reaction to obtain a hydrogel; the reaction monomers include hydroxypropyl acrylate, vinyl triethoxysilane, acrylic acid and polyethyleneimine;

[0009] The hydrogel is mixed with a dispersing solvent, and the obtained suspension is mixed with a tannic acid solution for modification to obtain a tannic acid-modified corrosion inhibitor-loaded gel material.

[0010] Preferably, the mass ratio of the reaction monomer, benzotriazole and initiator is 18-21:1-5:0.1-0.5;

[0011] The initiator includes azobisisobutyronitrile; and the organic solvent includes ethylene glycol methyl ether.

[0012] Preferably, the polymerization reaction temperature is 70-75° C. and the time is 2-3 hours.

[0013] Preferably, the mass ratio of the hydrogel to tannic acid in the tannic acid solution is 0.1-0.2:40; the pH value of the tannic acid solution is 7-8, and the concentration is 10-12 mol / L.

[0014] Preferably, the modification temperature is 23-25° C. and the modification time is 48-50 h.

[0015] The invention provides a tannic acid modified loaded corrosion inhibitor gel material prepared by the preparation method described in the technical scheme.

[0016] The present invention provides application of the tannic acid modified corrosion inhibitor loaded gel material described in the above technical solution in a self-repairing anti-corrosion coating.

[0017] Preferably, the application method comprises:

[0018] The tannic acid modified loaded corrosion inhibitor gel material, epoxy resin and curing agent are mixed, ultrasonic degassing treatment is performed, the obtained organic coating liquid is coated on the surface of the substrate, and cured to obtain a self-repairing anti-corrosion coating.

[0019] Preferably, the mass ratio of the tannic acid modified loaded corrosion inhibitor gel material, epoxy resin and curing agent is 0.05-0.2:7-11:9-12.

[0020] The present invention provides a method for preparing a tannic acid modified loaded corrosion inhibitor gel material. The present invention adopts a one-step free radical polymerization method to polymerize hydroxypropyl acrylate (HPA), vinyl triethoxysilane (VTEO) and acrylic acid (AA), and then encapsulates with polyethyleneimine (PEI) to synthesize a PHVA / PEI gel having the characteristics of pH sensitivity, high thermal stability and high compatibility with an organic coating. The surface of the PHVA / PEI gel is uneven with a large number of holes and wrinkles, so the PHVA / PEI gel is used as a carrier to prepare a hydrogel BTA@PHVA / PEI loaded with a corrosion inhibitor, which has the advantage of a high corrosion inhibitor loading amount. In addition, the tannic acid (TA) used in the present invention is a plant polyphenol with abundant sources, belongs to a green corrosion inhibitor, and can be combined with metal ions to form a tannic acid iron complex, and adsorbed on the metal surface to form a tannic acid iron film, delaying the corrosion process of the metal. Therefore, tannic acid was used to modify BTA@PHVA / PEI through the co-precipitation method, and the corrosion inhibitor loading and modification were carried out in steps. This has the advantages that the BTA@PHVA / PEI structure is not easily destroyed and the surface modification effect is good. The modifier tannic acid used can chelate with metal ions to form a passivation film on the surface of the metal matrix, thereby further slowing down the corrosion of the metal.

[0021] In the method of the present invention, the preparation of PHVA / PEI and the loading of BTA (benzotriazole) are carried out simultaneously, and the preparation process is simple.

[0022] The tannic acid modified loaded corrosion inhibitor gel material prepared by the present invention is added to the epoxy resin coating to prepare a self-repairing coating; the tannic acid modified loaded corrosion inhibitor gel material prepared by the present invention has good compatibility with the EP coating and good dispersibility in the coating, and the amount added to the coating can be increased, thereby improving the corrosion inhibition performance of the corrosion inhibitor BTA and improving the corrosion inhibition efficiency of the coating. In addition, the PHVA / PEI gel in the coating has pH responsiveness, so that the gel material responds to the pH value change caused by the corrosion reaction, and the corrosion inhibitor BTA molecules and TA molecules can be controlled and gradually released to achieve a self-repairing function. Moreover, the corrosion inhibitor loading amount of the gel material in the present invention is relatively high, so the prepared anti-corrosion coating has good self-repairing performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The SEM images of the PHVA / PEI gel in Comparative Example 1; (a) is a SEM image at a magnification of 10,000, and (b) is a SEM image at a magnification of 100,000;

[0024] Figure 2 The infrared spectra of TA, BTA@PHVA / PEI and TA@BTA@PHVA / PEI in Example 1;

[0025] Figure 3Thermogravimetric curves of PHVA / PEI in Comparative Example 1 and TA, BTA@PHVA / PEI and TA@BTA@PHVA / PEI in Example 1;

[0026] Figure 4 (a) Relationship between BTA absorption intensity and concentration; (b) BTA release rate curve of BTA@PHVA / PEI gel under different pH conditions;

[0027] Figure 5 Nyquist plots (a1) and Bode plots (a2) of coating samples TBP / EP, BP / EP, PP / EP and EP after immersion for 1 day;

[0028] Figure 6 Nyquist plots (a1) and Bode plots (a2) of coating samples TBP / EP, BP / EP, PP / EP and EP after immersion for 99 days;

[0029] Figure 7 Nyquist plot (a1) and Bode plot (a2) of coating samples TBP / EP, BP / EP, PP / EP and EP after immersion for 132 days. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing a tannic acid modified corrosion inhibitor loaded gel material, comprising the following steps:

[0031] Mixing reaction monomers, benzotriazole, an initiator and an organic solvent to carry out polymerization reaction to obtain a hydrogel; the reaction monomers include hydroxypropyl acrylate, vinyl triethoxysilane, acrylic acid and polyethyleneimine;

[0032] The hydrogel is mixed with a dispersing solvent, and the obtained suspension is mixed with a tannic acid solution for modification to obtain a tannic acid-modified corrosion inhibitor-loaded gel material.

[0033] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.

[0034] In the present invention, the mass ratio of the reaction monomer, benzotriazole (BTA) and initiator is preferably 18-21:1-5:0.1-0.5, more preferably 20:1-3:0.1-0.2; the reaction monomer includes hydroxypropyl acrylate, vinyl triethoxysilane, acrylic acid and polyethyleneimine; the amount ratio of hydroxypropyl acrylate (HPA), vinyl triethoxysilane (VTEO), acrylic acid (AA) and polyethyleneimine (PEI) is preferably 3.2g:5.5g:7.2g:3mL.

[0035] In the present invention, the initiator preferably includes azobisisobutyronitrile (AIBN); the organic solvent preferably includes ethylene glycol methyl ether. In the present invention, the usage ratio of hydroxypropyl acrylate (HPA) to the organic solvent is preferably 3.2g:30-50mL, more preferably 3.2g:40-50mL.

[0036] The present invention preferably adds HPA and an organic solvent into a flask, heats an oil bath to 70° C., introduces high-purity nitrogen, adds an initiator and BTA; after continuous stirring, drips vinyl triethoxysilane (VTEO) and acrylic acid (AA), and stirs at 70° C. for 2 hours; and then adds polyethyleneimine (PEI) to carry out a polymerization reaction.

[0037] In the present invention, the polymerization reaction temperature is preferably 70-75° C., more preferably 70° C., and the polymerization reaction time is preferably 2-3 h, more preferably 2 h.

[0038] After the polymerization reaction is completed, the present invention preferably vacuum-dries the obtained polymer at 60° C., soaks the obtained solid product in deionized water, freeze-dries it, and grinds it into powder to obtain a hydrogel, which is recorded as BTA@PHVA / PEI.

[0039] In the present invention, the dispersion solvent is preferably ethylene glycol methyl ether; the concentration of the hydrogel in the suspension is preferably 10 mg / mL; the pH value of the tannic acid solution is preferably 7-8, and the concentration is 10-12 mol / L; the tannic acid solution is preferably a tannic acid aqueous solution;

[0040] In the present invention, the mass ratio of the hydrogel to the tannic acid in the tannic acid solution is preferably 0.1-0.2:40, more preferably 0.1:40.

[0041] The present invention preferably adds the hydrogel into the dispersing solvent and stirs evenly to obtain a suspension; under vigorous stirring, adds the tannic acid aqueous solution into the suspension, stirs for 15 minutes, and then allows the obtained mixed solution to stand for modification.

[0042] In the present invention, the modification temperature is preferably 23-25° C., more preferably 24° C., and the modification time is preferably 48-50 h, more preferably 48 h.

[0043] After completing the modification, the present invention preferably centrifuges and washes the obtained product three times with a mixed solution of ethanol and water (ethanol: water = 1:9, volume ratio); the obtained precipitate is dried in a vacuum drying oven at 70° C. for 24 hours to obtain a tannic acid-modified loaded corrosion inhibitor gel material, recorded as TA@BTA@PHVA / PEI.

[0044] The invention provides a tannic acid modified loaded corrosion inhibitor gel material prepared by the preparation method described in the technical scheme.

[0045] The present invention provides application of the tannic acid modified corrosion inhibitor loaded gel material described in the above technical solution in a self-repairing anti-corrosion coating.

[0046] In the present invention, the application method preferably includes:

[0047] The tannic acid modified loaded corrosion inhibitor gel material, epoxy resin and curing agent are mixed, ultrasonic degassing treatment is performed, the obtained organic coating liquid is coated on the surface of the substrate, and cured to obtain a self-repairing anti-corrosion coating.

[0048] In the present invention, the mass ratio of the tannic acid-modified loaded corrosion inhibitor gel material, the epoxy resin and the curing agent is preferably 0.05-0.2:7-11:9-12, and more preferably 0.1:10:10.

[0049] The present invention has no special limitation on the specific types of the epoxy resin and curing agent, and any epoxy resin and curing agent for organic anti-corrosion coating known in the art can be used; in an embodiment of the present invention, the monomers of the epoxy resin are preferably bisphenol A diglycidyl ether and neopentyl glycol diglycidyl ether; and the curing agent is polyamide.

[0050] The present invention preferably adds the tannic acid modified loaded corrosion inhibitor gel material to the curing agent, stirs for 50 minutes and then ultrasonically treats the mixture until it is uniform; then adds the epoxy resin to the mixture, stirs the mixture evenly, and performs ultrasonic degassing treatment.

[0051] The present invention has no special limitation on the ultrasonic degassing treatment, the type of substrate and the curing conditions. A substrate well known in the art may be selected and the process well known in the art may be carried out. In an embodiment of the present invention, the substrate is Q235 carbon steel and is subjected to ultrasonic degassing treatment at 25°C for 2h.

[0052] In an embodiment of the present invention, the curing is preferably performed in a 50° C. oven (DHG-9023A) for 48 hours.

[0053] In the present invention, the thickness of the self-repairing anti-corrosion coating is preferably 90±5 μm.

[0054] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0055] Example 1

[0056] (1) 3.2 g HPA and 40 mL ethylene glycol methyl ether were added to a 250 mL three-necked flask, and a mechanical stirrer and a condenser were installed to start stirring; the oil bath was heated to 70° C., high-purity nitrogen (purity of 99.999%) was introduced, 0.1 g AIBN and 3.0 g BTA were added, and after continuous stirring, 5.5 g vinyl triethoxysilane (VTEO) and 7.2 g acrylic acid (AA) were added dropwise to the obtained reaction solution through a constant pressure funnel, and stirred at 70° C. for 2 h; 4 g polyethyleneimine (3 mL, PEI) was added, and the polymerization reaction was carried out for 2 h. After the reaction was completed, the obtained polymer was vacuum dried at 60° C., and the obtained solid product was soaked in deionized water, freeze-dried, and ground into powder to obtain BTA@PHVA / PEI;

[0057] (2) Add 0.1 g of BTA@PHVA / PEI to 10 mL of ethylene glycol methyl ether and stir evenly to obtain a suspension of BTA@PHVA / PEI;

[0058] (3) Under vigorous stirring, 2 mL of tannic acid aqueous solution (12 mol / L) with a pH of 8 was added to the above BTA@PHVA / PEI suspension, and the mixture was stirred for 15 min to obtain a mixed solution. The mixed solution was allowed to stand at 24°C for 48 h, and was centrifuged and washed three times with a mixed solution of ethanol and water (ethanol: water = 1:9, volume ratio). The obtained precipitate was dried in a vacuum drying oven at 70°C for 24 h to obtain TA@BTA@PHVA / PEI.

[0059] Example 2

[0060] (1) Add 3.2 g HPA and 40 mL ethylene glycol methyl ether to a 250 mL three-necked flask, install a mechanical stirrer and a condenser, and start stirring; heat the oil bath to 70° C., introduce high-purity nitrogen (purity of 99.999%), add 0.1 g AIBN and 1.0 g BTA, and continue stirring. Then, add 5.5 g vinyl triethoxysilane (VTEO) and 7.2 g acrylic acid (AA) dropwise to the obtained reaction solution through a constant pressure funnel, and stir at 70° C. for 2 h; add 4 g polyethyleneimine (PEI), and perform polymerization reaction for 2 h. After the reaction is completed, the obtained polymer is vacuum dried at 60° C., and the obtained solid product is soaked in deionized water, freeze-dried, and ground into powder to obtain BTA@PHVA / PEI;

[0061] (2) Add 0.1 g of BTA@PHVA / PEI to 10 mL of ethylene glycol methyl ether and stir evenly to obtain a suspension of BTA@PHVA / PEI;

[0062] (3) Under vigorous stirring, 2 mL of tannic acid aqueous solution (12 mol / L) with a pH of 8 was added to the above BTA@PHVA / PEI suspension, and the mixture was stirred for 15 min to obtain a mixed solution. The mixed solution was allowed to stand at 24°C for 48 h, and was centrifuged and washed three times with a mixed solution of ethanol and water (ethanol: water = 1:9, volume ratio). The obtained precipitate was dried in a vacuum drying oven at 70°C for 24 h to obtain TA@BTA@PHVA / PEI.

[0063] Example 3

[0064] (1) Add 3.2 g HPA and 40 mL ethylene glycol methyl ether to a 250 mL three-necked flask, install a mechanical stirrer and a condenser, and start stirring; heat the oil bath to 75° C., introduce high-purity nitrogen (purity of 99.999%), add 0.1 g AIBN and 1.0 g BTA, and continue stirring. Then, add 5.5 g vinyl triethoxysilane (VTEO) and 7.2 g acrylic acid (AA) dropwise to the obtained reaction solution through a constant pressure funnel, and stir at 70° C. for 2 h; add 4 g polyethyleneimine (PEI), and perform polymerization reaction for 2 h. After the reaction is completed, the obtained polymer is vacuum dried at 60° C., and the obtained solid product is soaked in deionized water, freeze-dried, and ground into powder to obtain BTA@PHVA / PEI;

[0065] (2) Add 0.1 g of BTA@PHVA / PEI to 10 mL of ethylene glycol methyl ether and stir evenly to obtain a suspension of BTA@PHVA / PEI;

[0066] (3) Under vigorous stirring, 2 mL of tannic acid aqueous solution (12 mol / L) with a pH of 8 was added to the above BTA@PHVA / PEI suspension, and the mixture was stirred for 15 min to obtain a mixed solution. The mixed solution was allowed to stand at 24°C for 48 h, and was centrifuged and washed three times with a mixed solution of ethanol and water (ethanol: water = 1:9, volume ratio). The obtained precipitate was dried in a vacuum drying oven at 70°C for 24 h to obtain TA@BTA@PHVA / PEI.

[0067] Comparative Example 1

[0068] The only difference from Example 1 is that no corrosion inhibitor BTA is added during the preparation of the gel. Other steps are the same as in Example 1 to obtain PHVA / PEI gel.

[0069] Characterization and performance testing

[0070] 1) Figure 1 The SEM images of the PHVA / PEI gel in Comparative Example 1, wherein (a) is a SEM image at a magnification of 10000, and (b) is a SEM image at a magnification of 100000. Figure 1It can be seen that the surface of PHVA / PEI gel is uneven with a large number of holes and wrinkles, which provides effective space for retaining moisture and loading corrosion inhibitor BTA.

[0071] 2) Figure 2 is the infrared spectra of TA, BTA@PHVA / PEI, and TA@BTA@PHVA / PEI in Example 1; Figure 2 It can be seen that the infrared spectra of BTA@PHVA / PEI and TA@BTA@PHVA / PEI are both at 1721 cm -1 The high-intensity peaks appearing near 927 cm are due to the stretching vibration of C=O in AA and HPA. -1 There is a significant characteristic absorption peak at 1404cm, which is mainly attributed to the stretching and bending vibration of Si-O-Si bond. -1 Another characteristic peak that appears nearby is due to the stretching vibration of the C-OH bond in AA and HPA molecules. -1 The strong absorption peaks near 1612cm are due to the vibration of -CH, -CH2 and -CH3 groups in the gel molecules. In the infrared spectrum of TA@BTA@PHVA / PEI, not only the characteristic peaks of BTA@PHVA / PEI can be seen, but also the peak of TA at 1612cm -1 The stretching vibration peak of the unsaturated aromatic C=C bond appeared nearby, indicating that TA modified BTA@PHVA / PEI successfully. -1 The absorption peak appearing at is the N=N characteristic peak of the BTA molecule, which can also be clearly observed in the spectrum of TA@BTA@PHVA / PEI, indicating that the TA modification does not affect the BTA loading.

[0072] 3) Figure 3 The thermogravimetric curves of PHVA / PEI in Comparative Example 1 and TA, BTA@PHVA / PEI and TA@BTA@PHVA / PEI in Example 1 are shown; Figure 3As shown in the figure, the thermal stability curves of TA@BTA@PHVA / PEI and BTA@PHVA / PEI can be divided into three stages. In the first stage, within the temperature range of 25℃~180℃, BTA@PHVA / PEI observed a mass loss of about 9%, while TA@BTA@PHVA / PEI had a mass loss of 10%, which was caused by the volatilization of water or unreacted solvent contained in the gel; in the second stage, the temperature weight loss area of ​​TA and TA@BTA@PHVA / PEI both appeared at 180℃~480℃. In this stage, the mass losses of TA and TA@BTA@PHVA / PEI were 58% and 53%, respectively, of which the mass loss of TA was mainly due to the decomposition of the benzene ring in TA, while the mass loss of TA@BTA@PHVA / PEI was due to the decomposition of TA, BTA and PEI, which made the mass loss of TA@BTA@PHVA / PEI higher. In the third stage, the temperature weight loss area of ​​TA and TA@BTA@PHVA / PEI both appeared at 480℃~800℃. At this stage, the mass loss of TA was 10%, which was due to the decomposition of the remaining aromatic compounds. TA@BTA@PHVA / PEI showed a mass loss of 7%, which was mainly related to the breakage of organic chains and the decomposition of siloxane. In summary, the synthesized TA@BTA@PHVA / PEI has good thermal stability. The reason is that the vinyl triethoxysilane in the monomer of the synthetic gel has a high bond energy in the siloxane structure, which enhances the thermal stability of the gel.

[0073] 4) Draw a standard concentration curve of BTA: Prepare 2 mg / L, 4 mg / L, 8 mg / L, 16 mg / L and 32 mg / L BTA standard solutions, and scan the UV-visible absorption spectrum of BTA. In addition, scan the UV-visible spectra of BTA and PHVA / PEI gel ( Figure 4 In the illustration of (a), 302 nm was selected as the quantitative concentration measurement point (the purpose is to eliminate the influence of PHVA / PEI gel on BTA concentration test). The linear fitting method was used to process the data, and the relationship between BTA concentration (Con) and absorption intensity (Abs) was obtained as shown in Formula 1:

[0074] Abs=0.04429 Con+0.18529 (1)

[0075] Figure 4(a) BTA absorption intensity and concentration relationship diagram, where the inset is the UV absorption spectra of PHVA / PEI gel and BTA; (b) BTA release rate curve of BTA@PHVA / PEI gel under different pH conditions (the UV-visible spectra of BTA@PHVA / PEI gel were measured at pH = 5, 7 and 10, and the intensity at 302 nm was selected to calculate the corresponding BTA concentration, and the Figure 4 The release curve in (b) shows that the first 4 hours is the rapid release period of BTA, and the release is most obvious under weak alkaline conditions. The cumulative release of BTA in the first 4 hours reaches 90%. Under the condition of pH 7, the release rate of corrosion inhibitor BTA is relatively slow, which helps to avoid premature leakage of BTA in the coating during the curing stage. It can be seen that BTA@PHVA / PEI gel can respond to pH changes in the external environment and has pH sensitivity.

[0076] In the following application example, a Q235 carbon steel sheet of 10 cm×10 cm×0.5 cm is used as a substrate for coating a self-repairing anti-corrosion coating (hereinafter referred to as a carbon steel substrate).

[0077] Application Example 1

[0078] The TA@BTA@PHVA / PEI prepared in Example 1 was added as a filler to the EP coating, and the specific steps were as follows:

[0079] 0.1 g of TA@BTA@PHVA / PEI prepared in Example 1 was added to 10 g of epoxy resin (specifically neopentyl glycol diglycidyl ether and bisphenol A diglycidyl ether in a mass ratio of 1:1.5), stirred for 50 min and then ultrasonicated until uniform; then, 10 g of curing agent (polyetheramine curing agent D230) was added to the mixed solution, stirred evenly, and ultrasonically degassed (25° C., ultrasonic time 2 h) to obtain an organic coating liquid;

[0080] Referring to GB / T 20777-2006 "Inspection and Preparation of Paint and Varnish Samples", the organic coating liquid was coated on the surface of the carbon steel substrate with a coating rod, the coated substrate was placed in an oven, and cured in an oven at 50°C (DHG-9023A) for 48 hours to prepare a self-healing anti-corrosion coating containing TA@BTA@PHVA / PEI on the carbon steel substrate, recorded as coating sample TBP / EP, with a coating thickness of 90 μm.

[0081] Application Example 2

[0082] The TA@BTA@PHVA / PEI in Application Example 1 was replaced by the BTA@PHVA / PEI prepared in Example 1, and the obtained sample was recorded as coating sample BP / EP.

[0083] Application Example 3

[0084] The TA@BTA@PHVA / PEI in Application Example 1 was replaced by the PHVA / PEI in Comparative Example 1, and the obtained sample was recorded as coating sample PP / EP.

[0085] Comparative application example 1

[0086] The only difference from Application Example 1 is that TA@BTA@PHVA / PEI is not added to obtain an EP coating.

[0087] Test the protective performance of the coating in application examples 1 to 3 and comparative application example 1

[0088] The coating samples TBP / EP, BP / EP, PP / EP and EP were immersed in 3.5wt.% NaCl solution, and the electrochemical impedance spectroscopy (EIS) of each coating sample at different immersion periods (1d, 99d, 132d) was tested using a CS310 electrochemical testing system (Wuhan Koster Instrument Co., Ltd.); the EIS test results of each coating sample at different immersion periods are shown in Figure 2. Figure 5 , Figure 6 and Figure 7 shown.

[0089] Figure 5 Nyquist plots (a1) and Bode plots (a2) of the coating samples TBP / EP, BP / EP, PP / EP and EP after immersion for 1 day; Figure 5 It can be seen that after immersion for 1 day, the coating impedances of the coating sample BP / EP, the coating sample TBP / EP and the EP coating are very close.

[0090] Figure 6 Nyquist plots (a1) and Bode plots (a2) of coating samples TBP / EP, BP / EP, PP / EP and EP after immersion for 99 days; Figure 6 It can be seen that after 99 days of immersion, the coating impedance of the coating sample BP / EP and the coating sample TBP / EP is significantly greater than that of the EP coating sample, indicating that the former has better protective performance. The coating impedance value of the coating sample TBP / EP is significantly greater than that of the coating sample BP / EP, which further indicates that TA modification has a positive effect on the protective performance of the coating.

[0091] Figure 7 Nyquist plots (a1) and Bode plots (a2) of the coating samples TBP / EP, BP / EP, PP / EP and EP after immersion for 132 days; Figure 7 It can be seen that after immersion for 132 days, the coating impedance of the coating sample TBP / EP is significantly greater than the coating impedance of the coating samples BP / EP and EP coating samples, indicating that the former has better protective performance.

[0092] In addition, by comparing the results of electrochemical impedance spectroscopy, it can be seen that both TA and BTA played a protective role, and TA did not affect the effect of BTA.

[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a tannic acid modified loaded corrosion inhibitor gel material, comprising the following steps: Mixing reaction monomers, benzotriazole, an initiator and an organic solvent to carry out polymerization reaction to obtain a hydrogel; the reaction monomers include hydroxypropyl acrylate, vinyl triethoxysilane, acrylic acid and polyethyleneimine; The hydrogel is mixed with a dispersing solvent, and the obtained suspension is mixed with a tannic acid solution for modification to obtain a tannic acid-modified corrosion inhibitor-loaded gel material.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the reaction monomer, benzotriazole and initiator is 18-21:1-5:0.1-0.5; The initiator includes azobisisobutyronitrile; and the organic solvent includes ethylene glycol methyl ether.

3. The preparation method according to claim 1 or 2, characterized in that: The polymerization reaction temperature is 70-75° C. and the reaction time is 2-3 hours.

4. The preparation method according to claim 1 or 4, characterized in that: The mass ratio of the hydrogel to the tannic acid in the tannic acid solution is 0.1-0.2:40; the pH value of the tannic acid solution is 7-8, and the concentration is 10-12 mol / L.

5. The preparation method according to claim 1, characterized in that: The modification temperature is 23-25° C. and the modification time is 48-50 hours.

6. The tannic acid-modified corrosion inhibitor-loaded gel material prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the tannic acid-modified corrosion inhibitor-loaded gel material according to claim 6 in a self-repairing anti-corrosion coating.

8. The use according to claim 7, characterized in that: The method of application includes: The tannic acid modified loaded corrosion inhibitor gel material, epoxy resin and curing agent are mixed, ultrasonic degassing treatment is performed, the obtained organic coating liquid is coated on the surface of the substrate, and cured to obtain a self-repairing anti-corrosion coating.

9. The use according to claim 8, characterized in that: The mass ratio of the tannic acid modified loaded corrosion inhibitor gel material, epoxy resin and curing agent is 0.05-0.2:7-11:9-12.

Citation Information

Cited By

  • BTA-loaded self-repairing anticorrosive coating and preparation method thereof

    CN119931462A